Comparing psychological constructs in early specializing and non-specializing youth boys hockey players - Mosher, A.; Baker, J.; Fraser-Thomas, J. (Current Issues in Sport Science, 2020)
Athletes who specialize early often invest more into their sport from a young age, thus it has been suggested early specializers may feel greater pressures to perform, and may have higher levels of anxiety. This study focused on better understanding the differences between early specializers and non-specializers in terms of psychological constructs (competitive state anxiety, competitive trait anxiety, and personality). Participants were divided into groups based on a modified version of the DHAQ (Hopwood, Baker, MacMahon & Farrow, 2010). Independent sample t-tests were conducted to test between group differences. There were no significant differences between early specializers and non-specializers in scores of competitive state anxiety, competitive trait anxiety, and the big five personality traits. Results highlight the need for further investigation into differences between early specializers and non-specializers.